A Shift in Authority. (1st May 2021) - Letourneau, Susan M.; Bennett, Dorothy; McMillan Culp, Katherine; Mohabir, Priya; Schloss, Dana; Liu, ChangChia James; Honey, Margaret
Abstract: Research across fields has converged on the importance of grounding STEM learning in learners' personal, social, and cultural experiences. This article describes how distributed and transformational leadership models in science centers can enable a paradigm shift away from unidirectional communication of scientific information from institution to visitor, and toward practices that prioritize the diversity of visitors' own experiences and their agency as learners and thinkers. Three case studies (on exhibit design, facilitation, and activity development) illustrate how adopting elements of distributed and transformational leadership models allowed project teams at the New York Hall of Science to operationalize the theoretical foundations of our museum's educational philosophy across multiple areas of the organization. Across the three projects, supporting visitors' agency and centering their diverse perspectives and prior knowledge required a parallel shift toward increased collaboration and agency among staff with diverse roles and areas of expertise.